Finance-dominated capitalism and income distribution: A Kaleckian perspective on the case of Germany - Eckhard Hein; Daniel Detzer (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2014)
We present an investigation into the long-run effects of financialisation on income distribution before the financial and economic crises for Germany, one of the major mercantilist export-led economies. The analysis builds on a Kaleckian approach towards the examination of the effects of financialisation on income distribution, as suggested by Hein (2014a). First, we show that Germany saw considerable re-distribution of income starting in early 1980s, which accelerated in the early 2000s, in particular. Examining the three main channels through which financialisation (and neo-liberalism) are supposed to have affected the wage or the labour income share, according to the Kaleckian approach, we provide evidence for the existence of each of these channels in Germany since the mid-1990s, when several institutional changes provided the conditions for an increasing dominance of finance.
Keywords: D31; D33; D43; 330; Finance-dominated capitalism; distribution of income; Kaleckian distribution theory; Germany